Pure and Dialogical Phenomenology - Geniušas, Saulius (Problemos, 2018)
[only abstract in English; full article and abstract in Lithuanian] The article strives to show why one needs to discard the common conception of phenomenology, according to which phenomenology is a peculiar form of reflection that is grounded in the first-person point of view. Rather, an investigation can be identified as phenomenological in the Husserlian sense of the term if, and only if, it is based on three fundamental phenomenological principles, viz., epoché, phenomenological reduction and eidetic variation. These principles must be conceived as three irreplaceable phenomenological principles that make up the basis of pure phenomenology. These three principles are necessary, yet they are not sufficient: they must be supplemented with the principle of factual variation. The article argues that the incorporation of the principle of factual variation into the field of phenomenological research transforms pure phenomenology into dialogical phenomenology.